Flexural strength of special reinforced lightweight concrete beam for Industrialised Building System (IBS) - Yip, Chun-Chieh (Penerbit UTM Press, 2015)
Special reinforced lightweight aggregate concrete (SRLWAC) beam is designed as beam component in Industrialised Building System (IBS). It is used to overcome the difficulties during the component installation due to the heavy lifting task. This paper presents the flexural strength and performance of SRLWAC beam under vertical static load. SRLWAC beam was set-up on two columns corbel and tested under monotonic vertical load. Five Linear Variable Displacement Transducers (LVDTs) were instrumented in the model to record displacement. The ultimate flexural capacity of the beam was obtained at the end of experiment where failure occurred. Performance of the beam was evaluated in load-displacement relationship of beam and mode of failure. SRLWAC beam was then modelled and simulated by nonlinear finite element software- Autodesk Simulation Mechanical. Result from finite element analysis was verified by experimental result. Maximum mid-span displacement, Von-Mises stress, concrete maximum principal stress, and yielding strength of reinforcement were discussed in this paper. The beam was behaved elastically up to 90 kN and deformed plastically until ultimate capacity of 250.1 kN in experimental test. The maximum mid span displacement for experimental and simulation were 15.21 mm and 15.36 mm respectively. The major failure of IBS SRLWAC beam was the splitting of the concrete and yielding of main reinforcements at overlay end. Ductility ratio of IBS SRLWAC beam was 14.2, which was higher than pre-stressed concrete beam.